ECOPEDAGOGY DALAM PENANAMAN GREEN CHARACTER MELALUI PROBLEM BASED LEARNING TENTANG PENGELOLAAN SAMPAH 3R DI SEKOLAH DASAR - Rohman, Akhmad Dalil; Asih, Tri Unggul Sari; Susanto, Nanang Hasan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Indonesia is still facing serious challenges in waste management. The World Bank’s Atlas of Sustainable Development Goals reported that Indonesia ranks fifth among the world’s largest waste-producing countries. Data from the National Waste Management Information System (SIPSN) of the Ministry of Environment and Forestry in July 2024 recorded a total of 35.1 million tons of national waste, with 38.6% (13.5 million tons) managed and 61.4% (21.6 million tons) unmanaged. This situation highlights the urgency of long-term solutions through education from an early age. This study aims to analyze the role of ecopedagogy in cultivating green character through the Problem Based Learning (PBL) model in the context of 3R (Reduce, Reuse, Recycle) waste management at the elementary school level. The study employed a library research method by reviewing primary and secondary sources such as journal articles, dissertations, proceedings, and official reports. Data were analyzed using content analysis techniques through reduction, classification, and synthesis of theories. The findings reveal that ecopedagogy serves as a philosophical foundation for ecological critical awareness, PBL as an active learning strategy based on real problems, and green character as the ultimate goal reflected in environmentally responsible behavior. The integration of these three aspects culminates in 3R practices in elementary schools, which not only enhance cognitive understanding but also foster affective attitudes and psychomotor skills. This study concludes that the integration of ecopedagogy, PBL, and green character can serve as an effective environmental education model for developing environmentally conscious and sustainable generations. ABSTRAKIndonesia masih menghadapi persoalan serius dalam pengelolaan sampah. Laporan World Bank’s Atlas of Sustainable Development Goals menyebutkan bahwa Indonesia merupakan penghasil sampah terbesar kelima di dunia. Data Sistem Informasi Pengelolaan Sampah Nasional (SIPSN) KLHK pada Juli 2024 mencatat jumlah timbunan sampah nasional mencapai 35,1 juta ton, dengan 38,6% atau 13,5 juta ton terkelola dan 61,4% atau 21,6 juta ton sisanya tidak terkelola. Kondisi ini menuntut adanya solusi jangka panjang melalui pendidikan sejak usia dini. Penelitian ini bertujuan untuk menganalisis peran ecopedagogy dalam penanaman green character melalui model Problem Based Learning (PBL) pada konteks pengelolaan sampah 3R (Reduce, Reuse, Recycle) di sekolah dasar. Penelitian ini menggunakan metode library research dengan menelaah berbagai literatur primer dan sekunder berupa artikel jurnal, disertasi, prosiding, dan laporan resmi. Analisis dilakukan dengan teknik analisis isi melalui reduksi, klasifikasi, dan sintesis teori. Hasil penelitian menunjukkan bahwa ecopedagogy berfungsi sebagai landasan filosofis kesadaran ekologis, PBL sebagai strategi pembelajaran berbasis masalah nyata, dan green character sebagai tujuan berupa perilaku peduli lingkungan. Integrasi ketiganya bermuara pada praktik pengelolaan sampah 3R di sekolah dasar yang tidak hanya meningkatkan pemahaman kognitif, tetapi juga menumbuhkan sikap afektif dan keterampilan psikomotorik siswa. Penelitian ini menyimpulkan bahwa integrasi ecopedagogy, PBL, dan green character dapat menjadi model pendidikan lingkungan yang efektif dalam membentuk generasi sadar lingkungan dan berkelanjutan.